POLICY IMPLEMENTATION OF THE PRIVATE DEVELOPMENT ASSESSMENT SYSTEM IN CLASS IIB PURWODADI INSTITUTION - Rachmad Adila; Odi Jarodi (Polteknik Ilmu Pemasyarakatan, 2022)
Correctional Institution is a Technical Implementation Unit (UPT) of the Directorate General of Corrections which is given the authority to carry out services, guidance and guidance to inmates in prison. With the emergence of a policy from the Ditjenpas regarding the Prisoners Guidance Assessment System (SPPN) which aims as a guide for correctional guardians in increasing the objectivity of assessing changes in prisoners' behavior, and supporting the fulfillment of prisoners' rights including remission, assimilation, parole (PB), conditional leave (CB). ) and other rights. The purpose of this study was to determine how the implementation of the SPPN policy, to know the supporting and inhibiting factors and to find out the efforts to overcome the obstacles to the SPPN policy in the Class IIB Purwodadi Prison. This study uses the study of the concept of George C. Edward III. This type of research is qualitative using descriptive method. Data was collected through observation, interviews, documentation and library studies. The results showed that the implementation of the SPPN policy in the Class IIB Purwodadi prison has not run optimally, because there are still problems in communication, namely the lack of communication between the correctional guardians and prisoners, human resources, namely the number of correctional guardians is not proportional to the number of prisoners, correctional guardians have not received training and education specifically related to the implementation of the SPPN policy. Supporting factors: Cooperation both internally and externally, support from superiors, utilization of infrastructure, friendly attitude of officers, good response from prisoners. Inhibiting factors: Limited time, multiple positions, workload, number of correctional guardians not proportional to the number of prisoners, lack of training, lack of infrastructure, insufficient budget/funds. Efforts in overcoming obstacles to the implementation of the SPPN policy are providing training and education to correctional guardians, providing rewards to correctional guardians, increasing cooperation both internally and externally, increasing the number of correctional guardians, utilizing infrastructure facilities.